Metal complexation capacity of Antarctic lacustrine sediments. (April 2018) - Alberti, Giancarla; Mussi, Matteo; Quattrini, Federico; Pesavento, Maria; Biesuz, Raffaela
Abstract: The purpose of this study is to implement a work that is a part of a project funded by the Italian National Antarctic Research Program (PNRA, Piano Nazionale di Ricerche in Antartide) within the main thematic focus "Chemical Contamination-Global Change". This research was devoted to detect and characterize micro and nano components with strong complexing capability towards metal ions at trace level in sea water, lakes and lacustrine sediments, sampled during the XXII expedition of PNRA. In particular, in the present work, the sorption complexation capacity of an Antarctic lacustrine sediments toward Cu(II) and Pb(II) is described. The characterization of the sorption was undertaken, studying kinetics and isotherm profiles. The lake here considered is Tarn Flat in the area of Terra Nova Bay. The sorption equilibria of Cu(II) and Pb(II) on the lacustrine sediments were reached in about 10 h, and they were best modelled by the Langmuir equation. Preliminary, to establish if the data here obtained were consistent with those reported for the same area in other expeditions, a common multivariate techniques, namely the principal component analysis (PCA), was applied and finally the consistency of the data has been confirmed. Graphical abstract: Image 1 Highlights: Determination of metal complexation properties of some natural organic and biologic substances. Method applied to Antarctic lacustrine sediments, within a main thematic project on "Chemical Contamination-Global Change". Results elaborated by multivariate statistical analysis, (Principal Component Analysis, PCA).